An investigation of the frequency of Kansas physical education teacher feedback and proximity in relation to student body mass index and gender - Ellis, Joyce A. (Kansas State University, 2007)
America is in the midst of an obesity epidemic (Wechsler, McKenna, Lee, & Dietz, 2004). According to Wechsler et al., physical inactivity is a major contributor to this issue. Burnette (1999), reports certain behaviors and instructional strategies help teachers to build stronger teaching/learning relationships with students, and that some specific behaviors may be the most influential. Teacher feedback and teacher proximity are two specific behaviors that are important in a physical education setting. Hastie (1998) and Lund (1990), report that when physical education teachers provide feedback and maintain proximity to students, learning may be enhanced. This study examined the frequency of teacher feedback and teacher proximity in relation to student body mass index (BMI) and student gender. Fifteen Kansas middle school physical education teachers were observed delivering skill based lessons to two classes of students. Event recording, a form of systematic observation, was used in data collection. A multivariate analysis of variance was conducted with independent samples T-tests conducted for specific demographic data. Results indicated no significant differences in the frequency of teacher feedback and teacher proximity in relation to student body mass index (BMI) or student gender. Results of the analysis of various pieces of demographic information showed teachers who use some of the Physical Focus Curriculum activities had a higher rate per minute of teacher feedback than teachers who use none of the curriculum. Analysis also showed that teachers using more individualized skill based activities provided significantly higher rates of feedback and proximity than those conducting large group activities. Further analysis of demographic data revealed those teachers currently coaching a sport provided less feedback and proximity to students in class than those not currently coaching. Membership in the state professional organization did not have any effect upon rates of teacher feedback or proximity. The effects of teacher gender on rates of feedback and proximity showed female teachers are more proximal to all students than male teachers. Recommendations to be considered when conducting further research include increasing the sample size, development of more specific instrumentation to measure rates of feedback and proximity in an activity setting, implementing more control of the type of activity and instruction provided, and including more diversity in the study.
Keywords: Teacher feedback; Teacher proximity; Body Mass Index; Physical Education; Obesity; Education, Physical (0523)